Identidades de papel. Identidad de la ausencia y negación de los migrantes indocumentados: un enfoque desde tres textos narrativos (Altre Modernità, 2014)
Starting from the analysis of three narrative texts – the novels of Mexican author Alejandro Hernández, Amarás a Dios sobre todas las cosas (2013) [You shall love God above all things] and the Uruguayan writer Jorge Majfud, Crisis (2012), and thirdly the short story by Nicaraguan author Sergio Ramirez, Abbot y Costello (2013) [Abbot and Costello] – this study ventures into the realities of undocumented migrants who experience their identity in terms of “absence”, due to the lack of legal acknowledgment. The condition of being “paperless” places the migrant in a particular state that locates him in a classification where a general – negative and exclusive – idea prevails, and standardizes thousands and thousands of human beings based on their shortcomings, in a process of depersonalization.     Absence becomes the official identity mark and configures the identity features of this segment of the population starting from its weakness, impotence and vulnerability, thereby making these aspects of frailty the constitutive feature of its identity. The “undocumented” create an self-identity rooted in negation from and of themselves, by making the image that the others have of them into their own image, and by getting caught in the game of making themselves invisible and being perceived as invisible.     The discursive texts analysed here explore these spaces of absence and invisibility that surround the discourse of the “paperless” and their experiences. They also contribute to investigating and questioning – in a territory that has remained almost unexplored so far – the issue of the annihilated identity that hopes to be able to be and to exist one day.